2017
DOI: 10.1001/jama.2017.4342
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of the US Medicare Annual Wellness Visit, 2011-2014

Abstract: This study has several limitations. Claims data could not show how often AWVs were performed by nonphysicians under physician supervision, and the extent to which AWVs represent delivery of additional visits vs substitution for other visits remains unclear. More research is needed on whether AWVs increase use of preventive care or mitigate health risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 6 publications
6
73
0
1
Order By: Relevance
“…The group completing the survey was heterogeneous, consisting of members who chose to complete an annual wellness visit, as well as Medicaid Special Needs Plan members who CMS required to complete an annual assessment. This selection bias may have affected our estimate of the prevalence of food insecurity, although a higher proportion of KPCO members completed Medicare annual wellness visits than has been reported in other settings . Third, food insecurity was assessed using a single item whose validity has not been compared with more standard measures such as the 18‐item or 6‐item U.S. Department of Agriculture measures or the 2‐item Hunger Vital Sign .…”
Section: Discussionmentioning
confidence: 99%
“…The group completing the survey was heterogeneous, consisting of members who chose to complete an annual wellness visit, as well as Medicaid Special Needs Plan members who CMS required to complete an annual assessment. This selection bias may have affected our estimate of the prevalence of food insecurity, although a higher proportion of KPCO members completed Medicare annual wellness visits than has been reported in other settings . Third, food insecurity was assessed using a single item whose validity has not been compared with more standard measures such as the 18‐item or 6‐item U.S. Department of Agriculture measures or the 2‐item Hunger Vital Sign .…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that the use of AWVs rose from about 7% (3.2 million visits) in 2011 to 20% (10.4 million visits) in 2016. 1 The utilization rates in 2016 vary from about 7% in Hawaii to 33% in Rhode Island. In 2014, The AWV utilization rates in non-Hispanic whites were 45% and 88% percent higher, respectively, than African Americans and Hispanics, and the rates in metropolitan residents were about 60% higher than rural residents.…”
Section: Introductionmentioning
confidence: 99%
“…Annual Wellness Visits ** encompass personalized prevention plan services including a comprehensive health risk assessment, assessments to detect cognitive impairment, diabetes, hypertension, and missed vaccinations ( 8 , 9 ). However, these Medicare prevention and wellness benefits are not as widely used by older Americans as they could be; in 2013, only 6.8% of new Medicare enrollees took advantage of the Welcome to Medicare visit ( 10 ), and in 2014, approximately 16% of Medicare recipients had an Annual Wellness Visit; only an estimated 7% of Medicare beneficiaries receive all recommended preventive services ( 9 , 11 ). Annual Wellness Visit barriers include the relatively long duration of the visit (1 hour), low reimbursement rate for providers, and patient confusion about what is included in the visit ( 11 ).…”
mentioning
confidence: 99%
“…However, these Medicare prevention and wellness benefits are not as widely used by older Americans as they could be; in 2013, only 6.8% of new Medicare enrollees took advantage of the Welcome to Medicare visit ( 10 ), and in 2014, approximately 16% of Medicare recipients had an Annual Wellness Visit; only an estimated 7% of Medicare beneficiaries receive all recommended preventive services ( 9 , 11 ). Annual Wellness Visit barriers include the relatively long duration of the visit (1 hour), low reimbursement rate for providers, and patient confusion about what is included in the visit ( 11 ). The U.S. Department of Health and Human Services established improving the rates of the Welcome to Medicare visits as an important Healthy People 2020 objective ( 10 ).…”
mentioning
confidence: 99%